2021
DOI: 10.1186/s40246-021-00341-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes associated with prognosis, diagnosis, immune infiltration and therapeutic drug in liver cancer by integrated analysis

Abstract: Background Liver cancer is one of the most common cancers and causes of cancer death worldwide. The objective was to elucidate novel hub genes which were benefit for diagnosis, prognosis, and targeted therapy in liver cancer via integrated analysis. Methods GSE84402, GSE101685, and GSE112791 were filtered from the Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) were identified by using the GEO2R. The GO and KEGG pathway of DEGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Users can fully explore the clinical and genomic characteristics of tumors with TIMER's ( https://cistrome.shinyapps.io/timer/ ) comprehensive analysis of immune infiltrates of different cancer types [ 31 ]. We examined the correlation of hub genes in CRA and CRC with six immune cells: B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Users can fully explore the clinical and genomic characteristics of tumors with TIMER's ( https://cistrome.shinyapps.io/timer/ ) comprehensive analysis of immune infiltrates of different cancer types [ 31 ]. We examined the correlation of hub genes in CRA and CRC with six immune cells: B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Coincidently, previous studies have reported a close relationship between increased expression of ANXA2 , 31 EGLN3 , 32 GAS2L3 , 33 MKI67 , 31 MMP12 , 34 NQO1 35 and PTTG1 36 genes and poor survival in HCC tumors, while variants of PPP1RB gene have been associated with liver steatosis and increased risk of developing liver cancer 37 . Since our comparison revealed INMT as the most downregulated gene (Supplementary Table S5), we analyzed its expression among the 371 cases from the TCGA database.…”
Section: Resultsmentioning
confidence: 56%
“…Numerous studies demonstrated that tumor microenvironment in uences BC development, invasion, and metastasis. In addition, previous study indicated that MDSCs [37], cancer associated broblasts (CAFs) and the extra cellular matrix (ECM) changes are crucial for BC from happens to metastasis [38]. Those supported that CDK1 possibly plays an important role in immune in ltration and even metastasis.…”
Section: Discussionmentioning
confidence: 95%